Anxiety Rebalance: All The Answers You Need to Overcome Anxiety and Depression - Carl Vernon (Headline, 2016)
Anxiety Rebalance is Carl Vernon's personal experience of overcoming 15 years of crippling anxiety. In this online best-seller, Carl combines a compelling account of his experience with the answers he found, including the 10 key actions that helped him achieve balance. The response from his readers (of his original self-published edition) has been extraordinary, and his solutions will become as much as a life manual as Feel the Fear and Do It Anyway and Sane New World. 'Throughout the fifteen years I battled with anxiety and depression I was constantly looking for a cure - until I realised I was looking for answers that didn't exist. Don't waste another minute.' Dealing with anxiety requires ONE thing: BALANCE Carl's step-by-step guide teaches you: The truth about anxiety and depression - by exposing them for what they really are. How to instantly reduce your stress and anxiety, and feel immediate relief. How to control all anxiety-related symptoms and disorders including panic attacks, social anxiety, OCD and agoraphobia. Why BALANCE is the only real solution for overcoming anxiety and depression, Plus the 10 actions you need to take to achieve lifetime change. Where do you come on the ReBalance scale?